1988
DOI: 10.3109/00365518809088765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the serum lipid-lowering effect of n-3 fatty acids

Abstract: Both epidemiological and experimental studies have demonstrated that a high content of n-3 fatty acids in the diet lowers serum lipid concentration. However, the mechanism for this effect is unclear. In this present study it has been shown that labelled linolenic acid (18:3, n-3) is oxidized to a larger extent than linoleic acid (18:2,n-6) in isolated rat hepatocytes. Conversely, the incorporation of linolenic acid and the desaturated/chain-elongated products in VLDL-triacylglycerol is decreased compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ikeda et al [35] suggested that in rats, fish oil depresses TAG secretion from the liver. Hagve and Christophersen [36] reported that n-3 fatty acids were more readily converted to ketone bodies than n-6 fatty acids in cultured hepatocyte. Moreover, fish oil supplementation increased blood concentrations of ketone bodies in human subjects [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ikeda et al [35] suggested that in rats, fish oil depresses TAG secretion from the liver. Hagve and Christophersen [36] reported that n-3 fatty acids were more readily converted to ketone bodies than n-6 fatty acids in cultured hepatocyte. Moreover, fish oil supplementation increased blood concentrations of ketone bodies in human subjects [37].…”
Section: Discussionmentioning
confidence: 99%
“…The lipostatic effect of n-3 fatty acids has been explained by impaired hepatic triglyceride and subsequently VLDL synthesis (19,35). Thus, n-3 fatty acids are known to suppress both hepatic triacyiglycerol synthesis and VLDL secretion (19). In cultured rat hepatocytes, EA inhibits microsomal acyl-coenzyme A: 1.2 diacylglycerol acyltransferase and acyl-coenzyme A: cholesterol acyltransferase.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…On the other hand, any lipostatic compound which blocks hepatic very low density lipoprotein (VLDL)-production as n-3 fatty acids do (19,35), might also interfere with substrate cycling by shifting more non-esterified fatty acids (NEFA) to 3-oxidation and thus impairing glucose tolerance (4,33). However, only one study has so far directly compared the metabolic effects of n-3 fatty acids with those of a conventional lipostatic therapy in non-diabetic hyperlipidemic cardiac transplant recipients (5).…”
Section: Introductionmentioning
confidence: 99%